Reform and Exploration of Multidimensional Aviation Service Teaching Mode Based on OBE - Li, Yu (Applied mathematics and nonlinear sciences, 2024)
In order to ensure that relevant aviation talents have solid professional theoretical knowledge, it is necessary to raise the importance of teaching aviation theory courses in talent cultivation and lay the foundation for the improvement of the quality of aviation service talent cultivation. Based on OBE theory, this paper designs a multidimensional aviation service teaching model that encompasses four aspects: curriculum system, strategy, goal, and evaluation. Subsequently, the teaching model is applied to carry out service thinking teaching in G school, designing the service thinking development trajectory analysis framework to excavate the service thinking evolution process, characterizing the service thinking development law of student groups through the FCM clustering algorithm and visualization technology, and exploring the characteristics implied by the service thinking development law of different groups. Results: The service thinking ability of students of all labels under the OBE-based multidimensional aviation service teaching method was significantly improved, and all of them improved by at least 0.3 points, and the presentation and sharing part of teaching played a greater role in the development of students’ service thinking ability. In addition, the scores of students’ group resilience, self-control, and service dimensions under this model are more concentrated in the 20-30 points area, and most students in language and cooperation dimensions are still under 20 points, and the development of “all-round” dimensions is better than that of other labeled students.